2018
DOI: 10.1146/annurev-clinpsy-050817-084847
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Scores in Clinical Psychology: Bridging Genomic Risk to Individual Differences

Abstract: Genomewide association studies (GWASs) across psychiatric phenotypes have shown that common genetic variants generally confer risk with small effect sizes (odds ratio < 1.1) that additively contribute to polygenic risk. Summary statistics derived from large discovery GWASs can be used to generate polygenic risk scores (PRS) in independent, target data sets to examine correlates of polygenic disorder liability (e.g., does genetic liability to schizophrenia predict cognition?). The intuitive appeal and generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 226 publications
8
102
2
Order By: Relevance
“…Increased VS activity and dopamine release to non-alcohol reward have been associated with substance use initiation and problematic drinking. While the proportion of explained variance is modest, it is consistent with other PRS analyses 89 and supports the generalizability of our findings at a polygenic level. 87 These apparently disparate findings can be integrated with stage-based theories of addiction, which hypothesize that initial problematic use is associated with the positive reinforcing aspects of a substance, while later compulsive use is driven by negative reinforcement and diminished cognitive control, resulting from changes in neural plasticity induced by chronic alcohol use 88 Despite these potential differences, for 2 of the 5 loci (rs1229984 and rs188227250), meta-analyses across samples yielded more significant associations.…”
Section: Discussionsupporting
confidence: 91%
“…Increased VS activity and dopamine release to non-alcohol reward have been associated with substance use initiation and problematic drinking. While the proportion of explained variance is modest, it is consistent with other PRS analyses 89 and supports the generalizability of our findings at a polygenic level. 87 These apparently disparate findings can be integrated with stage-based theories of addiction, which hypothesize that initial problematic use is associated with the positive reinforcing aspects of a substance, while later compulsive use is driven by negative reinforcement and diminished cognitive control, resulting from changes in neural plasticity induced by chronic alcohol use 88 Despite these potential differences, for 2 of the 5 loci (rs1229984 and rs188227250), meta-analyses across samples yielded more significant associations.…”
Section: Discussionsupporting
confidence: 91%
“…Substantial advances in molecular genetics technology and increased sample sizes have allowed researchers to examine polygenic contributions to phenotypes, correlates and outcomes associated with educational attainment (ie, number of years of schooling) . However, most of the research in this area has included individuals of European descent, although there are a few exceptions .…”
Section: Introductionmentioning
confidence: 99%
“…Substantial advances in molecular genetics technology and increased sample sizes have allowed researchers to examine polygenic contributions to phenotypes, correlates and outcomes associated with educational attainment (ie, number of years of schooling). 1 However, most of the research in this area has included individuals of European descent, although there are a few exceptions. [2][3][4] This is a significant issue as it is unclear whether and to what extent findings from genome-wide association studies (GWAS) involving individuals of European ancestry apply to individuals of different ancestral backgrounds given differences in allele frequencies and linkage disequilibrium (LD) structure across ancestry groups.…”
Section: Introductionmentioning
confidence: 99%
“…For cannabis use, the largest published study to date (n = 184 765 individuals of European descent [19]; results used here on n = 162 082; see Supporting information for details) identified four independent genome-wide significant loci and found a genome-wide single nucleotide polymorphism (SNP) heritability of 10%, suggesting that the aggregated effects of common SNPs captured a sizeable proportion of the heritability of cannabis use. PRS approaches are widely used in psychiatric genetics, including substance use and dependence, and can be used to assess whether genetic risk for one disorder or trait is associated with aspects of the same trait or with a correlated disorder/trait [21,22]. In brief, a PRS is a person-specific index of genetic propensity to a trait (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…cannabis use); PRS are constructed by multiplying the effect size from a discovery GWAS by the number of risk alleles that an individual possesses at that SNP. PRS approaches are widely used in psychiatric genetics, including substance use and dependence, and can be used to assess whether genetic risk for one disorder or trait is associated with aspects of the same trait or with a correlated disorder/trait [21,22]. For instance, one study found that PRS for schizophrenia risk predicted cannabis use in individuals with bipolar disorder [23].…”
Section: Introductionmentioning
confidence: 99%